Kepercayaan Lintas Generasi Dalam Penggunaan Social Media dan Electronic Word of Mouth - Dewa Ayu Ketut Bintang Arbina Swari; Gede Sri Darma (Universitas Pendidikan Nasional, 2019)
ABSTRACTThis study aims to examine how much influence the use of social media, electronic word of mouth and trust as an intermediary variable and about the factors that influence hotel consumer purchasing decisions in the digital era 4.0, where trust is an intermediate variable. The increasing number of competitors raises the enthusiasm of business people to further improve their services. Tourism is one sector that plays an important role in national economic growth. The current conditions faced by companies engaged in lodging service providers are how to change offline marketing strategies leading to online marketing to optimize room occupancy rates. The population used in this study is all Balinese people who are domestic consumers who have stayed at hotels in Bali. Data collection is done using the online questionnaire method through Google Form. The sampling method in this study is convenience sampling, where sampling is based on the availability of elements and the ease of obtaining them. The number of samples used in this study were 100 people. The analysis technique used to analyze the data is SEM (Structural Equation Model). The results of this study indicate, (1) the usage of social media variable to trust is a positive and significant effect that has a standardized estimate (regression weight) of 0.333, (2) the usage of social media variable to purchase decision involvement is a positive and significant effect that has a standardized estimate (regression weight) of 0.089, (3) the electronic word of mouth variable to trust is a positive and significant effect that has a standardized estimate (regression weight) of 0.315, (4) the electronic word of mouth variable to purchase decision involvement is a positive and significant effect which has a standardized estimate (regression weight) of 0.089, (5) the variable Subjective Age for trust is a positive and significant effect which has a standardized estimate (regression weight) of 0.439, (6) the variable Subjective Age to purchase decision involvement is a positive and significant effect that has standardize estimate (regression weight) of 0.319, (7) the variable trust in purchase decision involvement is a positive and significant effect that has a standardized estimate (regression weight) of 0.494.